Pregnancy disorders in female workers at the industrial area of Sidoarjo, Indonesia - Firman Suryadi Rahman; Tri Martiana (SAGE Publishing, 2020)
Background: The number of female workers in Indonesia has increased and female workers have been discovered to be very vulnerable to several hazards and health problems in the workplace environment linked to their menstrual cycle and pregnancy. Therefore, this study was conducted to analyze risk factors associated with pregnancy disorders in female workers. Design and Methods: The research was conducted through the use of a cross-sectional design with 307 female workers using simple random sampling. Furthermore, a descriptive analysis was conducted to describe the conditions of the respondents during pregnancy to childbirth process. Results: The results showed 45% of respondents had pregnancy disorders, 16% had miscarriages, and despite the fact most of the prenatal care processes was assisted by doctors or midwives, 2.6% of the respondents consulted Traditional Birth Attendants, who were also recorded and was found to account for 2.9% of the deliveries. Moreover, the risk factors associated with pregnancy disorders include vibrations (P=0.004), irritants (P=0.002) and repetitive works (P=0.009). Conclusions: It is recommended that companies should provide maternal and child health protection and control for any risk associated with female workers.